Impact of a COVID-19 related lockdown on the experience of informal caregiving in Singapore - QIN, Vicky Mengqi (Institutional Knowledge at Singapore Management University, 2024)
Introduction: Lockdowns, while limiting COVID-19 transmission, can affect provision of care by informal caregivers and their caregiving experience. We assessed, among informal caregivers in Singapore, (a) the perceived impact of a 2-month (April to May 2020) nationwide lockdown on their care provision, (b) correlates of different perceptions of the impact of the lockdown on care provision, and (c) association of different perceptions of the impact with negative and positive experiences of caregiving. Methods: In the August 2020 wave of the Singapore Life Panel (SLP; nationally representative, longitudinal monthly survey of Singapore citizens and permanent residents aged 50-70 years at baseline), 1,094 participants identified as informal caregivers reported whether their care provision became easier, remained the same, or became harder during the lockdown, compared to before the lockdown. We used multinomial logistic regression to assess the association of caregiver, care recipient, and caregiving context characteristics with their perceptions. Linear regression models examined the association of their perceptions with negative and positive experience domains of the modified Caregiver Reaction Assessment. Results: Just over one-third (36.1%) of the informal caregivers reported that their care provision became harder during the lockdown compared to before the lockdown. However, nearly one-fifth (18.0%) said that it became easier, and the rest (45.9%) said that it remained the same. Care provision was more likely to be perceived as having become harder among caregivers who were male, of Chinese ethnicity, in worse health, whose care recipients had functional limitations, who did not have caregiving support from cohabiting family members before the lockdown, and who had caregiving support from non-cohabiting family members before the lockdown. The perception that care provision became easier was less likely among caregivers who were of higher age, were unemployed, were socially isolated, and whose care recipients had functional limitations. Caregivers who perceived that care provision became harder during the lockdown were worse-off in negative experiences of caregiving. Conclusion: A nationwide lockdown did not make care provision harder for all informal caregivers. However, informal caregivers for whom it did were more likely to have greater negative experiences of caregiving. The heterogeneity of the impact of lockdowns and the possibility of offering flexibility to non-cohabiting family members who support caregiving should be important considerations when planning for such disruptions.